Liberal Spaces: The Costs and Contradictions of Reproducing Hegemonic National Subjects in Ang Lee’s The Wedding Banquet and Brokeback Mountain - Olutola, Sarah (Atlantis, 2015)
Focusing on director Ang Lee’s films The Wedding Banquet and Brokeback Mountain, this paper explores the ways in which Lee’s articulation of queer intimacy in liberal spaces reproduces the regulatory functions of patriarchal, late-capitalist Eurocentric discourses of modernity.